An insight into the vaginal microbiome of infertile women in Bangladesh using metagenomic approach - Hasan, Zahid; Netherland, Michael; Hasan, Nur A.; Begum, Nurjahan; Yasmin, Mahmuda; Ahmed, Sangita (Frontiers in Cellular and Infection Microbiology, 2024)
Dysbiosis of the vaginal microbiota is recognized as one of the underlying reasons behind infertility problems in women. This study compared the vaginal microbiome in infertile and fertile women, to examine its relationship with infertility. A metagenomic analysis of 5 infertile and 5 fertile individuals was performed, employing amplicon 16S and metagenomics shotgun sequencing. Three major bacterial genera, Lactobacillus (79.42%), Gardnerella (12.56%) and Prevotella (3.33%) primarily represented the bacterial community in the infertile group, whereas fertile group comprised over 8 major bacterial genera with significantly reduced abundance of Lactobacillus (48.79%) and Gardnerella (6.98%). At the species level, the infertile group constitutes higher abundances of L. iners, L. gasseri and G. vaginalis. Only one healthy and two infertile subjects exhibited the healthiest Community State Types of the microbiome profiles, CST-1, whereas CST-3 was observed among two infertile and one healthy subject, and CST-4 in three other healthy and one infertile subject. Overall, the alpha diversity metrics indicated greater diversity and lower species richness in the Healthy group, while the infertile group displayed the opposite. Beta-diversity analysis did not show distinct clustering of samples associated with any group. Rather, it demonstrated CST-type specific clustering of the samples. Shotgun metagenomics reaffirmed the dominance of Firmicutes, with a greater abundance of Lactobacillus species in the infertile group. At species level, L. iners and G. vaginalis were the most dominant and highly abundant in infertile cases. Fungi were only identified in the control group, dominated by Penicillium citrinum (62.5%). Metagenome-assembled genomes of study and healthy public samples corroborated read-based taxonomic profiling. The taxon L. johnsonii was the only MAG exclusive to disease samples. MAG identities shared by two groups include Shamonda orthobunyavirus, L. crispatus, Human endogenous retrovirus K113, L. iners, and G. vaginalis. The healthy microbiomes sequenced in this study contained two clusters, Penicillium and Staphylococcus haemolyticus, not found in the public dataset. This study indicates towards lower species diversity with a higher abundance of L. iners, L. gasseri and G. vaginalis, as a contributing factor to female infertility in our study datasets, though larger sample size is required to further evaluate such association.